Preliminary Studies on the Seasonal Occurrence of Insect Pests on Soap-nut (Sapindus Sp.) - Subba Rao, A. (Indian Forester, 1992)
Survey for the seasonal occurrence, nature of damage and intensity of infestation of insect pests of soap-nut around Bapatla revealed that blossom webber (Cydia sp.) is the most destructive pest causing very severe damage during October-April followed by the fruit feeders Virachola isocrates F., Virachola sp, Serinatha augur Fabr. and Antilochus cogueberti Fabr. from January-April. Soap-nut moth, soap-nut tree bug and weevils were of moderate importance.